2021
DOI: 10.3311/ppch.16869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Side Groups on the Hydrolytic Stability of Thiolated and Disulfide Cross-linked Polyaspartamides

Abstract: Thiolated polyaspartamides either with N,N-dimethyl-2-aminoethyl (DME), N,N-dimethyl-3-aminopropyl (DMP) or 2-hydroxyethyl (HE) side groups were synthesized to study the effect of side groups on the hydrolytic stability of these polymers. The chemical structure of linear polymers was confirmed by 1H NMR spectroscopy, while thiol content was determined by Ellman's assay. Hydrolytic stability of thiolated polyaspartamides was studied by viscosity measurements and results suggested main-chain degradation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Various types of carriers, such as hydrogels [39], liposomes [40], and nanoparticles (NPs) [41][42][43], have been used for this purpose. Different inorganic NPs (such as, silica, iron and titan-oxide NPs), and organic NPs (for example natural and unnatural polymer NPs such as polyvinyl alcohol (PVA), polylactic acid (PLA), chitosan, polyaspatamodes) single enzyme NPs, and carbon-based NPs (such as graphene and carbon nanotubes) can all be utilized in enzyme therapy formulation [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of carriers, such as hydrogels [39], liposomes [40], and nanoparticles (NPs) [41][42][43], have been used for this purpose. Different inorganic NPs (such as, silica, iron and titan-oxide NPs), and organic NPs (for example natural and unnatural polymer NPs such as polyvinyl alcohol (PVA), polylactic acid (PLA), chitosan, polyaspatamodes) single enzyme NPs, and carbon-based NPs (such as graphene and carbon nanotubes) can all be utilized in enzyme therapy formulation [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…We earlier reported that poly(aspartic acid) and polyaspartamide derivatives and their hydrogels are promising candidates as biocompatible, chemically versatile, and responsive excipients. [18][19][20][21][22][23] We also showed that the non-enzymatic degradation rate of polyaspartamide hydrogels could be controlled by the side group structure, 24 making disulfide cross-linked PASP hydrogels good candidates for human biological applications where in situ gelation and/or bioadhesion are beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrin units have already been conjugated to various macromolecular structures to obtain water-soluble polymer-based formulations or hydrogels for the efficient encapsulation of hydrophobic APIs [27]. Poly(aspartic acid) (PASP) and its thiolated form as water-soluble, biodegradable, and biocompatible poly(amino acid)s are widely studied for pharmaceutical uses [28][29][30][31][32][33]. The interest in using PASP is supported by the chemical versatility of polysuccinimide − the precursor polymer of PASP − as succinimide repeating units can react with various nucleophiles and facilitate degradation under physiological conditions depending on the composition of the pendant groups [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%